THE RESULTS OF THE PANCREATODUODENECTOMY IN THE SPECIALIZED DEPARTMENT OF A GENERAL HOSPITAL - M. L. Rogal; P. A. Ivanov; P. A. Yartsev; A. N. Smolyar; E. A. Kiselyov (Неотложная медицинская помощь)
BACKGROUND Pancreatoduodenal resection (PDR) is the only radical method of treatment in patients with malignancies of the head of pancreas, terminal part of the common bile duct, duodenum, and major duodenal papilla. That is why the demand for this operation is very high.PURPOSE OF THE STUDY To reason the possibility and necessity of PDR in a general hospital.MATERIAL AND METHODS We studied 55 patients aged from 29 to 75 years who had undergone PDR. In 27 (49%) patients, cancer of the head of pancreas was an indication for surgery. The tumor of the terminal part of the common bile duct was diagnosed in 12 (21%) cases, major duodenal papilla — in 2 (3%) cases. Complicated chronic pancreatitis was the indication for operation in 15 (27%) cases.RESULTS Postoperative complications were mild or average, lethal outcomes did not occur. Failure of the pancreatic-digestive anastomosis was the most common complication (8 patients). Most postoperative complications have been cured by mini invasive methods.CONCLUSION PDR is possible, and in many cases advisable to be performed in a multidisciplinary institution, with relevant experience and technical equipment, as it provides much greater possibilities of treatment for both surgical and non-surgical complications.